2016
DOI: 10.20452/pamw.3384
|View full text |Cite
|
Sign up to set email alerts
|

What is more affected in patients wit obstructive sleep apnea: the right or the left heart?

Abstract: EDITORIAL What is more affected in patients with obstructive sleep apnea: the right or the left heart? 217 diameter, suggesting that severe OSA may cause pulmonary artery dilation.Taken these original and interesting studies together, we have observed a common limitation, likely due to an ethical issue. Indeed, both papers did not evaluate pulmonary arterial pressure by right cardiac catheterization, nor evaluated the left ventricular alterations, so we could not clarify the exact associations among the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…34, 35 Hernandez et al 24 demonstrated that positive effects of CPAP treatment on the melatonin concentration defined as shift of the peak serum melatonin level from 6 AM to 2 AM can be seen as early as on the first day of CPAP use. We did not find significant differences between serum melatonin concentrations at any of the analyzed time points after 2 days of treatment with CPAP.…”
Section: Methodsmentioning
confidence: 99%
“…34, 35 Hernandez et al 24 demonstrated that positive effects of CPAP treatment on the melatonin concentration defined as shift of the peak serum melatonin level from 6 AM to 2 AM can be seen as early as on the first day of CPAP use. We did not find significant differences between serum melatonin concentrations at any of the analyzed time points after 2 days of treatment with CPAP.…”
Section: Methodsmentioning
confidence: 99%
“…These anatomical conditions are linked with recurrent obstruction of the pharyngeal airway during sleep, with resultant hypoxia and sleep fragmentation, leading to a persistent long‐term risk for several cardio‐pulmonary diseases, in subjects affected by OSA 2 . Chronic upper airways inflammation constantly promotes a systemic endothelial dysfunction 3,4 that worsens the cardio‐pulmonary activity, thus, affecting the left and the right heart performance, 5 increases risk of cardiovascular events, over time 6 …”
Section: Introductionmentioning
confidence: 99%